Early Evidence of Shifts in Alpine Summit Vegetation: A Case Study From Kashmir Himalaya - Hamid, Maroof; Khuroo, Anzar Ahmad; Malik, Akhtar Hussain; Ahmad, Rameez; Singh, Chandra Prakash; Dolezal, Jiri; Haq, Shiekh Marifatul (Frontiers in Plant Science, 2020)
Under the contemporary climate change, the Himalaya is reported to be warming at a much higher rate than the global average. However, little is known about alpine vegetation responses to recent climate change in the rapidly warming Himalaya. Here we studied vegetation dynamics on alpine summits in Kashmir Himalaya in relation to in-situ measured microclimate. The summits, representing an elevation gradient from treeline to nival zone (3530 to 3740 m), were first surveyed in 2014 and then re-surveyed in 2018. The initial survey showed that the species richness, vegetation cover and soil temperature decreased with increasing elevation. Species richness and soil temperature differed significantly, with east and south slopes showing higher values than north and west slopes. The re-survey showed that species richness increased on the lower three summits but decreased on the highest summit (nival zone) and also revealed a substantial increase in cover of shrubs, graminoids and forbs. The nestedness-resultant dissimilarity, rather than species turnover, contributed more to the magnitude of β-diversity among the summits. High temporal species turnover was found on south and east aspects, while high nestedness was recorded along north and west aspects. Thermophilization was more pronounced on the lower two summits and along the northern aspects. Our study provides crucial scientific data on climate change impacts on the alpine vegetation of Kashmir Himalaya, which will bridge global knowledge gaps from the developing world.